Analysis of Lift and Drag of Mono-foil Hysucat due to Longitudinal Foil-placement Variation - Suastika, Ketut; Dikantoro, Regi Y.; Purwanto, Dedi B.; Setyawan, Dony; Putra, Wing H. A. (International Journal of Marine Engineering Innovation and Research, 2018)
CFD simulations were conducted to study the effects of a hydrofoil and its relative placement in the longitudinal direction on the total resistance of a mono-foil hysucat (hydrofoil supported catamaran). Three foil positions were considered: (i) precisely below the vessel’s center of gravity, (ii) 3 chord-lengths aft from position 1 and (iii) 6 chord-lengths aft from position 1. At relatively low speed (volumetric Froude number FnV < 1.8), the hydrofoil results in an increase of the total resistance of the hysucat (up to 4.43%). At relatively high speed (FnV > 1.8), the hydrofoil results in a decrease of the total resistance (up to 34.86%). The resistance coefficient first increases, takes a maximum value and then decreases with increasing Froude number. The maximum value is observed at FnV ≈ 1.4 (or Fn ≈ 0.5), consistent with previous observations. The most optimum foil placement is that precisely below the center of gravity of the vessel.